2022
DOI: 10.1038/s41598-022-13417-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of plasma circulating tumor DNA and tumor DNA profiles in head and neck squamous cell carcinoma

Abstract: Early recurrence detection of head and neck squamous cell carcinoma (HNSCC) is important for improving prognosis. Recently, circulating tumor DNA (ctDNA) has been reported to be useful in early detection or treatment response determination in various carcinomas. This study aimed to identify the utility of ctDNA for predicting recurrent metastasis in patients with HNSCC. We collected pre-treatment tissues (malignant and normal tissues) and multiple plasma samples before and after treatment for 20 cases of HNSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…One of the few studies using tumor‐derived ctDNA in head and neck oncology published by Chikuie et al 22 studied its utility in cancer surveillance. Their study included 20 patients and they reported the presence of ctDNA in 5 out of the 7 patients that had a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies using tumor‐derived ctDNA in head and neck oncology published by Chikuie et al 22 studied its utility in cancer surveillance. Their study included 20 patients and they reported the presence of ctDNA in 5 out of the 7 patients that had a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…52 Studies have shown that ctDNA levels are elevated in patients with HNC and can be used to monitor disease progression and response to treatment. 53 In addition, ctDNA has been found to be a prognostic marker, with higher levels associated with poorer outcomes. The use of liquid biomarkers in HNC is still in the early stages of development, and more research is needed to determine their clinical utility.…”
Section: Surveillance/survivorshipmentioning
confidence: 99%
“…Several liquid biomarkers have been identified in HNC, including circulating tumor cells, cell-free tumor DNA (ctDNA), proteins, metabolites, exosomes, messenger RNA (mRNA), and micro RNAs (miRNAs) 52 . Studies have shown that ctDNA levels are elevated in patients with HNC and can be used to monitor disease progression and response to treatment 53 . In addition, ctDNA has been found to be a prognostic marker, with higher levels associated with poorer outcomes.…”
Section: Surveillance/survivorshipmentioning
confidence: 99%